2011
DOI: 10.4067/s0718-50732011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Monitoreo mediante EIS del acero embebido en un concreto de escoria activada alcalinamente expuesto a carbonatación

Abstract: Monitoreo mediante EIS del acero embebido en un concreto de escoria activada alcalinamente expuesto a carbonatación * Universidad Militar Nueva Granada, Bogotá. COLOMBIA ** Universidad Pedagógica y Tecnológica de Colombia, Tunja-Boyacá. COLOMBIA Resumen En este trabajo se utilizó la técnica de espectroscopia de impedancia electroquímica (EIS) para evaluar la acción del dióxido de carbono sobre la corrosión de un acero estructural ASTM A 706 embebido en un concreto de escoria activado alcalinamente (AAS), el co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Given the degree of air pollution and CO2 in the main cities, one can expect concrete structures to show advanced states of carbonation. According to pathology studies on buildings and bridges in big cities, some structures were shown deterioration from rebar corrosion attributable to carbonation [5] [6]. Due to the greater porosity of cement pastes with a high water-to-cement ratio, the impact of carbonation on the structure increases.…”
Section: Introductionmentioning
confidence: 99%
“…Given the degree of air pollution and CO2 in the main cities, one can expect concrete structures to show advanced states of carbonation. According to pathology studies on buildings and bridges in big cities, some structures were shown deterioration from rebar corrosion attributable to carbonation [5] [6]. Due to the greater porosity of cement pastes with a high water-to-cement ratio, the impact of carbonation on the structure increases.…”
Section: Introductionmentioning
confidence: 99%